ANALISIS PERBANDINGAN EFISIENSI MODAL KERJA ANTARA PT. MAYORA INDAH Tbk. DAN PT. SIANTAR TOP Tbk. YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nur, Sri Wahyuni (Economos : Jurnal Ekonomi dan Bisnis, 2021)
Working capital is one of the most important asset elements in the company. Because without working capital, the company cannot meet the funding needs to carry out its activities. The working capital turnover period is since cash is invested in working capital elements until it becomes cash again. It is less than one year or short-term. This working capital turnover period shows the level of efficiency in the use of working capital. This research aims to determine which company is more efficient in using working capital between PT. Mayora Indah Tbk. and PT. Siantar Top Tbk. In this research, the data collection techniques used were 1) Documentation, this method is used to obtain information in the form of secondary data that refers to documents related to the working capital efficiency of PT. Mayora Indah Tbk and PT. Siantar Top Tbk. 2) Literature Research, namely data collection techniques by conducting searches using references from books, journals, and papers correlated to the research object for obtaining concepts and data relevant to the problems research as research support. The analytical method used is the descriptive analysis method with financial ratio analysis, where the financial ratio used is the activity ratio, namely the working capital turnover ratio. Based on the research results, PT. Mayora Indah Tbk. Obtaining an average working capital turnover of 3.61 times or 4 times for 5 years, while PT. Siantar Top, Tbk of - 182.14. Therefore, it concludes that PT. Mayora Indah Tbk is more efficient in using its working capital than PT. Siantar Top Tbk.